Democratização da gestão e conselho escolar: o caso de uma escola pública no município de Ipubi/ PE - Pereira, Antonio Cezar (2016)
The School Board has been considered one of the main instruments for the process of democratization of management. It is seen as a possibility of participation of all school segments in building a pedagogical proposal founded on democratic principles seeking pedagogical, administrative and financial autonomy. This paper analyzes the implementation, operation and contributions of Paulo Freire School Board of the School Little Prince - Ipubi- PE for the democratization of management and for school and everyday social life. Our objective was to analyze how is the participation and organization of the said school Board and the contribution of the Council for management. Discusses concepts of democracy, participation and management as well as relevant aspects of the implementation of the Council on public schools and at the school. This is a qualitative research with case study, where minutes of meetings were analyzed, legal documents and interviews with members of the School Board. The study results indicated little participation in decisions of the Council or school deliberations focusing their work only in the financial and legal issues relevant to the operation of the school unit. The main difficulty in the performance of the council is the lack of time to attend meetings and lack of previous scheduling them. Although the research subjects, recognizing the importance of the Council as a forum for participation and school democratization, the way it is conducted and the discontinuity of the meetings has prevented the contribution becomes effective within a vision of democratic management. The subjects indicated as a suggestion the disclosure of an agenda and provided an agenda which also discuss pedagogical issues and situations of everyday school life.